Early contraceptive discontinuation and associated factors among married women initiating long-acting and short-acting contraceptives in humanitarian settings in Ethiopia: A retrospective cohort study - Andamlak Gizaw Alamdo; Agnes M. Kotoh; Emefa Judith Modey; Juliana Yartey Enos (PLoS ONE, 2026)
Background The sexual and reproductive health (SRH) service provision in conflict-affected populations has been continually overlooked. International and local relief organizations have begun to recognize the neglect of women’s SRH needs; however, SRH services and humanitarian responses remain suboptimal. Contraceptive discontinuation is a significant public health issue with considerable impact on family planning (FP) programs, as well as on women’s SRH and population growth. There is scarce information regarding the dynamics of contraceptive use in refugee areas. Evidence on contraceptive use dynamics is vital, especially now, as the global refugee crisis grows. Therefore, this study aimed to examine first-year contraceptive discontinuation and associated factors among married women initiating long-acting reversible contraceptives (LARC) and short-acting contraceptives (SAC) in selected refugee populations in Ethiopia. Methods A retrospective cohort study was conducted among 551 married women in selected refugee populations in Ethiopia. After reviewing FP registries, all eligible women who initiated a contraceptive method 12–18 months before data collection were included in the study. Through computer-assisted face-to-face interviews, data on the socio-demographic, reproductive, and contraceptive use history of women were collected. Key characteristics of SAC acceptors and LARC acceptors were compared using chi-square statistics and t-tests. A multivariable Cox proportional hazards model identified the predictors of time to contraceptive discontinuation during the first year of use. In addition, adjusted hazard ratios (aHR), 95% CI, and P-values were calculated to determine the magnitude and precision of the association. Results The 12-month discontinuation rate for all contraceptive methods was 41.2% (95% CI: 37.2–45.4). The discontinuation rate for SAC (44.94%) was higher than LARC (32.32%) (P ≤ 0.001). The factors associated with 12-month discontinuation include method type (aHR = 1.50;95% CI:1.06–2.12), residence (aHR = 1.83;95% CI:1.24–2.70), husband occupation (aHR = 0.49;95% CI:0.29–0.84), length of stay in the refugee camp (aHR = 0.95;95% CI:0.92–0.99), and intention to use contraceptives in the future (aHR = 0.15;95% CI:0.11–0.21). Conclusion A high rate of early contraceptive discontinuation was documented among refugee women, with a higher discontinuation rate among SAC acceptors. To improve contraceptive service provision and maintain continuous use of the methods initiated, targeted interventions, such as improved counselling and promotion of long-acting contraceptive methods, especially among urban refugee women, are crucial.